Western Balkans Regular Economic Report No. 12, Fall 2017 : Job Creation Picks Up - World Bank Group (World Bank, Washington, DC, 2017)
This is a semi-annual report series on recent economic developments and economic policies in the Western Balkans (Albania, Bosnia and Herzegovina, Kosovo, FYR Macedonia, Montenegro, and Serbia). The report looks at the economic performance and outlook for the Western Balkans region and specific factors that affect the growth prospects.